Supplication in English and Arabic: A Contrastive Study - Mehdi, Manar Kareem (Advances in Social Sciences Research Journal, 2021)
From a religious standpoint, supplication is an act of worship that enables man to enrich his relationship with his Creator, the Almighty Allah. The essence of supplication is to revive Allah’s remembrance inside man’s heart. Moreover, supplication makes clear the fact that man is imperfect, poor and needy to his Lord, the Perfect, the Rich, and the One Who needs nobody at all (Al-Ameedi and Mahdi, 2014: 23). Linguistically, to supplicate, Vanderveken (1990:192) states, is to beg in a very humble manner usually from a superior or someone in power. Accordingly, the present paper aims to find out the syntactic components that constitute the syntactic structure of the act of supplication in English and Arabic highlighting the similarities and differences between the two languages in this regard. Hence, the paper hypothesizes that: (1) the vocative, the imperative, and parallelism constitute the basic syntactic components in English and Arabic supplication; (2) Arabic is more explicit than English in the linguistic realization of the act under scrutiny. Findings of the analysis verify the above mentioned hypotheses.